Presumed Fuchs Heterochromic Iridocyclitis and Posner-Schlossman Syndrome: Comparison of Cytomegalovirus-Positive and Negative Eyes - Chee, Soon-Phaik; Jap, Aliza (American journal of ophthalmology, 2008)
To compare the characteristics of cytomegalovirus (CMV)-positive and negative eyes with presumed Posner-Schlossman syndrome (PSS) and Fuchs heterochromic iridocyclitis (FHI). Retrospective interventional case series. One hundred and three eyes of 102 patients with presumed PSS or FHI, seen at the Singapore National Eye Centre, underwent aqueous analysis for CMV by polymerase chain reaction (PCR). Their records were reviewed for clinical features and human immunodeficiency virus (HIV) status of the CMV-positive patients. The main outcome measures were age, gender, maximum intraocular pressure, endothelial cell count, endothelial changes, PCR results, and presence of uveitic cataract and/or glaucoma. Sixty-seven eyes with presumed PSS were tapped, of which 35 (52.2%) were CMV-positive. There were 36 eyes of 35 patients with presumed FHI, of which 15 (41.7%) were CMV-positive. All the CMV-positive patients were HIV negative. Nodular endothelial lesions were seen in 18 eyes (36.0%) with CMV infection, and reticulate deposits were seen in all the presumed FHI eyes. CMV-positive and CMV-negative PSS eyes were clinically similar. Older age at diagnosis, male gender, and nodular endothelial lesions were significantly associated with CMV infection in presumed FHI eyes (age: odds ratio [OR], 1.1; 95% confidence interval [CI], 1.0 to 1.2; P = .01; male gender: OR, 9.4; 95% CI, 1.0 to 88.6; P = .049; nodular endothelial lesions: OR, 13.9; 95% CI, 1.5 to 132.7; P = .02). There are no clinically detectable differences between CMV-positive and negative presumed PSS eyes. CMV-positive presumed FHI patients are more likely to be male, older at diagnosis or have nodular endothelial lesions.